Javanese Culture Ewuh Pakewuh Among Educators - Wijayanti, Mega Putri (Syntax Corporation Indonesia, 2024)
In modern times, there is still a situation where people are reluctant to express opinions or reprimand friends whose behavior is not good. This situation has become a habit called ewuh pakewuh in Javanese culture. This culture influences the professionalism of individual and organizational work among educators. Ewuh pakewuh has a psychological aspect that is closely related to the principles of harmony and respect related to aspects of masculinity organizational culture, namely assertiveness. The positive impact of the Ewuh Pakewuh Culture is the respectful and polite behavior of junior educators to seniors as an effort to learn to be good and professional educators, able to express opinions, be firm and assertive, on the other hand the negative impact of the Ewuh Pakewuh Culture is respectful and polite behavior which is defined as obedience. which requires junior educators not to be assertive, afraid to refuse seniors' requests. This article was created to find out the positive and negative impacts of Ewuh Pakewuh culture among educators.